La adquisición del español como lengua extranjera por aprendientes francófonos de África: implicaciones teóricas y pedagógicas - Sossouvi, Laurent-fidèle (Didáctica. Lengua y Literatura, 2009)
This article deals with the errors of one hundred Beninese students of Spanish as Foreign Language (SFL) and, specifically, with its causes in order to contribute to the debate about the teaching / learning process of languages, like Spanish and German for example, which use tends to merely limit in the classroom. We propose to examine the adjustment of this process to the context of social and individual multilinguism that is Benin in the light of the (socio) linguistic practices typically associated to it. We suggest that these practices can motivate a different interpretation from both the factors surrounding the teaching / learning process and, mainly, the errors that characterize the output of the learners.En francés: Cet article traite des erreurs de cent apprenants béninois d'Espagnol comme langue étrangère (ELE) et, spécifiquement, ses causes afin de contribuer au débat sur l'enseignement/ apprentissage des langues, comme l’espagnol et l'Allemand, dont l'utilisation tend à se limiter à la salle de classe. Nous proposons d'examiner l'ajustement de ce processus au contexte multiethnique, multilingue social et individuel qu’est le Bénin à la lumière des pratiques (socio) linguistiques observées dans ce pays. Nous suggérons que ces pratiques puissent motiver une interprétation différente aussi bien des facteurs entourant l'enseignement/ apprentissage que, des erreurs qui caractérisent la production des apprenants.
Keywords: Error analysis; Contact of languages; Error; Interference; Code-mixing; Multilinguism Analyse d'erreur; Contact des langues; Erreur; Interférence; Mélange de codes; Multilinguisme